Two Step Selection for Bias in β Chain V-J Pairing - Levi, Reut; Louzoun, Yoram (Frontiers in Immunology, 2022)
The β chain rearrangement in T cells is a two-step process where first Dβ and Jβ bind, and only then Vβ is joined to the complex. We here show that the frequency of human and mouse Vβ Jβ combinations deviates from the one expected based on each gene usage frequency. This bias is observed mainly in functional (F) rearrangements, but also slightly in non-functional (NF) rearrangements. Preferred Vβ Jβ combinations in F clones are shared between donors and samples, suggesting a common structural mechanism for these biases in addition to any host-specific antigen-induced peripheral selection. The sharing holds even in clones with Jβ1 that share the same Dβ1 gene. Vβ Jβ usage is correlated with the Molecular Weight and Isoelectric Point in F clones. The pairing is also observed in the Double Positive cells in mice thymocytes, suggesting that the selection leading to such a pairing occurs before thymic selection. These results suggest an additional structural checkpoint in the beta chain development prior to thymic selection during the T cell receptor expression. Understanding this structural selection is important for the distinction between normal and aberrant T cell development, and crucial for the design of engineered TCRs.